Small and Intermediate Calcium-Activated Potassium Channel Openers Improve Rat Endothelial and Erectile Function - Comerma-Steffensen, Simon G.; Carvacho, Ingrid; Hedegaard, Elise R.; Simonsen, Ulf (Frontiers in Pharmacology, 2017)
Modulation of endothelial calcium-activated potassium (KCa) channels has been proposed as an approach to restore endothelial function. The present study investigated whether novel openers of KCa channels with small (KCa2.x) and intermediate (KCa3.1) conductance, NS309 and NS4591, improve endothelium-dependent relaxation and erectile function. Rat corpus cavernosum (CC) strips were mounted for isometric tension recording and processed for immunoblotting. Mean arterial pressure (MAP), intracavernosal pressure (ICP), and electrocardiographic (ECG) measurements were conducted in anaesthetized rats. Immunoblotting revealed the presence of KCa2.3 and large KCa conductance (KCa1.1) channels in the corpus cavernosum. NS309 and NS4591 increased current in CC endothelial cells in whole cell patch clamp experiments. Relaxation induced by NS309 (<1 µM) was inhibited by endothelial cell removal and high extracellular potassium. An inhibitor of nitric oxide (NO) synthase, and blockers of KCa2.x and KCa1.1 channels, apamin and iberiotoxin also inhibited NS309 relaxation. Incubation with NS309 (0.5 µM) markedly enhanced acetylcholine relaxation. Basal erectile function (ICP/MAP) increased during administration of NS309. Increases in ICP/MAP after cavernous nerve stimulation with NS309 were unchanged, whereas NS4591 significantly improved erectile function. Administration of NS309 and NS4591 caused small changes in the electrocardiogram, but neither arrhythmic events nor prolongation of the QTc interval were observed. The present study suggests that openers of KCa2.x and KCa3.1 channels improve endothelial and erectile function. The effects of NS309 and NS4591 on heart rate and ECG are small, but will require additional safety studies before evaluating whether activation of KCa2.3 channels has a potential for treatment of erectile dysfunction.